2014
DOI: 10.1016/j.bbmt.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Single Infusion of Donor Mononuclear Early Apoptotic Cells as Prophylaxis for Graft-versus-Host Disease in Myeloablative HLA-Matched Allogeneic Bone Marrow Transplantation: A Phase I/IIa Clinical Trial

Abstract: Because of its potent immunomodulatory effect, an infusion of donor mononuclear early apoptotic cells (ApoCell) was tested in addition to cyclosporine and methotrexate as prophylaxis for acute graft-versus-host disease (GVHD) after HLA-matched myeloablative allogeneic hematopoietic stem cell transplantation (HSCT) from a related donor. In a phase I/IIa clinical trial, we treated 13 patients (median age, 37 years; range, 20 to 59 years) with hematologic malignancies: 7 patients with acute lymphoblastic leukemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 30 publications
2
64
0
1
Order By: Relevance
“…A Phase I/IIa clinical trial has been performed in 13 patients without specific future science group Review Saas, Kaminski & Perruche toxicities and a good early outcome has been observed [127]. This confirms the feasibility of such cell-based therapy approaches in humans.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…A Phase I/IIa clinical trial has been performed in 13 patients without specific future science group Review Saas, Kaminski & Perruche toxicities and a good early outcome has been observed [127]. This confirms the feasibility of such cell-based therapy approaches in humans.…”
Section: Resultsmentioning
confidence: 76%
“…In experimental models (Table 3), infusion of apoptotic cells at time of transplantation induces TGF-b and increases Tregs that prevent GvHD occurrence [14,117,120]. Recently, a Phase I/IIa clinical study has been registered [201] and encouraging data have been presented recently in two meetings [126,127]. In this study, iv.…”
Section: Hematopoietic Engraftmentmentioning
confidence: 89%
See 1 more Smart Citation
“…Graft-versus-host disease (GVHD) is one of the major complications after allogeneic HSCT [1][2][3]. The standard GVHD prophylaxis regimen is a combination of methotrexate (MTX) and a calcineurin inhibitor, such as cyclosporine A (CSA) or tacrolimus (TAC) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting incidence of grade II to IV GVHD was 23% (with 0% for the 2 highest cell doses) and nonrelapse mortality was 8% at day 100. 9 Incubation of host DCs with these apoptotic cells also significantly decreased the cell surface expression of the activation markers HLA-DR and CD86. Future clinical trials of cellular therapy with apoptotic cells (potentially of either donor or host origin) to prevent GVHD will therefore be of great interest.…”
mentioning
confidence: 95%